Permian nappe tectonics and high-grade metamorphism related to Gondwanide Orogeny in northern Patagonia terrane. - González, Pablo Diego (2021)
Fil: González, Pablo Diego. Consejo Nacional de Investigaciones Científicas y Técnicas (CONICET), Argentina. Servicio Geológico Minero Argentino, Centro General Roca, Río Negro, SEGEMAR Regional Sur, Independencia 1495, Parque Industrial 1, Gral. Roca, (Río Negro), C. P. 8332, Casilla, Correo, Argentina.